Effect of Titanium, Silver and Zinc Nanoparticles on Microalgae in the Aquatic Environment - Thenarasu A.; Kin C.M.; Shing W.L.; Djearamane S.; Thirunavukkarasu C. (Editorial board of Journal of Experimental Biology and Agricultural Sciences, 2023)
Metallic nanoparticles (MNPs) are commonly incorporated in products found in households, industries, and agriculture. The presence of MNPs in the aquatic environment causes damage to living organisms and pollutes the water body rendering it harmful for human consumption. Several studies have been made on the toxicity of MNPs toward microalgae. Most of these studies reported changes in the cellular structure, growth rate, pigments, proteins, and enzymatic activity of microalgae. This review paper focuses on the toxic effects of titanium, zinc, and silver nanoparticles on microalgae in the aquatic environment. A better understanding of the behavior of MNPs in the ecosystem will allow scientists to produce environmentally safe MNPs. 2022, Editorial board of Journal of Experimental Biology and Agricultural Sciences. All rights reserved.